Chemoselective Hydrogenation of Nitroaromatics at the Nanoscale Iron(III)–OH–Platinum Interface. (25th May 2020) - Wang, Yu; Qin, Ruixuan; Wang, Yongke; Ren, Juan; Zhou, Wenting; Li, Laiyang; Ming, Jiang; Zhang, Wuyong; Fu, Gang; Zheng, Nanfeng
Abstract: Catalytic hydrogenation of nitroaromatics is an environment‐benign strategy to produce industrially important aniline intermediates. Herein, we report that Fe(OH) x deposition on Pt nanocrystals to give Fe(OH) x /Pt, enables the selective hydrogenation of nitro groups into amino groups without hydrogenating other functional groups on the aromatic ring. The unique catalytic behavior is identified to be associated with the Fe III ‐OH‐Pt interfaces. While H2 activation occurs on exposed Pt atoms to ensure the high activity, the high selectivity towards the production of substituted aniline originates from the Fe III ‐OH‐Pt interfaces. In situ IR, X‐ray photoelectron spectroscopy (XPS), and isotope effect studies reveal that the Fe 3+ /Fe 2+ redox couple facilitates the hydrodeoxygenation of the ‐NO2 group during hydrogenation catalysis. Benefitting from Fe III ‐OH‐Pt interfaces, the Fe(OH) x /Pt catalysts exhibit high catalytic performance towards a broad range of substituted nitroarenes. Abstract : Iron supplements : Deposition of Fe(OH) x on Pt nanoparticles created Fe III ‐OH‐Pt interfaces, which combine the facile dissociation of H2 on Pt with the hydrodeoxygenation process of the Fe 3+ /Fe 2+ redox cycle, thus facilitating the chemoselective hydrogenation of a broad range of substituted nitrobenzenes to the corresponding anilines without hydrogenating other substituents.